2013
DOI: 10.1371/journal.pone.0071570
|View full text |Cite
|
Sign up to set email alerts
|

Stress Reaction in Outer Segments of Photoreceptors after Blue Light Irradiation

Abstract: The retina is prone to oxidative stress from many factors which are also involved in the pathogenesis of degenerative diseases. In this study, we used the application of blue light as a physiological stress factor. The aim of this study was to identify the major source of intracellular ROS that mediates blue light-induced detrimental effects on cells which may lead to cytotoxicity. We hypothesized that outer segments are the major source of blue light induced ROS generation. In photoreceptors, nicotinamide ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 37 publications
3
85
0
1
Order By: Relevance
“…In the light-induced model of photoreceptor degeneration in mouse, superoxide radicals and other ROS contribute to photoreceptor apoptosis 25 and RAC1 has been linked to photoreceptor cell loss. 40,63 A recent study 64 has found that NOX mediates ROS generation and oxidative damage in mouse photoreceptors after blue light damage. In addition, RAC1-NOX–dependent superoxide generation is responsible for light-induced degeneration of Crumbs-deficient photoreceptor cells in Drosophila .…”
Section: Discussionmentioning
confidence: 99%
“…In the light-induced model of photoreceptor degeneration in mouse, superoxide radicals and other ROS contribute to photoreceptor apoptosis 25 and RAC1 has been linked to photoreceptor cell loss. 40,63 A recent study 64 has found that NOX mediates ROS generation and oxidative damage in mouse photoreceptors after blue light damage. In addition, RAC1-NOX–dependent superoxide generation is responsible for light-induced degeneration of Crumbs-deficient photoreceptor cells in Drosophila .…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial membrane potential. Mitochondrial membrane potential (MMP) was assessed by measuring the potential-dependent accumulation of 5,5=,6,6=-tetrachloro-1,1=,3,3=-tetraethylbenzimdazol carbocyanine iodide (JC-1; Molecular Probes) or tetramethylrhodamine ethyl ester (Invitrogen-Molecular Probes) (27). As previously described (1), the isolated mitochondrial pellet and dissociated podocytes were washed twice with HBSS (Sigma) and then incubated in the dark with JC-1 (7.5 M) for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…It was performed to see the level of expression of GFAP, AQP1 and AQP4 in the retina among the three experimental groups (N = 24, 8 retina/group, Table 1 [40,41]. The specificity of the antibodies was also confirmed by performing Western blot of proteins extracted from rat retina.…”
Section: Western Immunoblottingmentioning
confidence: 99%